Interrupted CuAAC-thiolation for the construction of 1,2,3-triazole-fused eight-membered heterocycles from O-/N-propargyl derived benzyl thiosulfonates with organic azides - Reddy, Raju Jannapu; Waheed, Md; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2022)
A copper(I)-catalyzed interrupted click-sulfenylation of O-/N-propargyl benzyl thiosulfonates with organic azides has been disclosed. The unified CuAAC-thiolation provides a wide range of triazole-fused eight-membered heterocycles in good to high (51-94%) yields under mild reaction conditions. Moreover, a three-component reaction is also achieved involving O-/N-propargyl benzyl thiosulfonates, benzyl bromide, and sodium azide to deliver fused-triazoles in 61-74% yields. From a synthetic point of view, the present protocol has been demonstrated at gram-scale reactions. A plausible mechanism is also proposed based on experimental results and control experiments.
Keywords: Eight-Membered Heterocycles; Fused-Triazoles; Interrupted-Click Reaction; Thiolation; thiosulfonates